Colorimetrics: Colorimetric Plasmon Resonance Imaging Using Nano Lycurgus Cup Arrays (Advanced Optical Materials 1/2013). Issue 1 (31st January 2013) - Gartia, Manas Ranjan; Hsiao, Austin; Pokhriyal, Anusha; Seo, Sujin; Kulsharova, Gulsim; Cunningham, Brian T.; Bond, Tiziana C.; Liu, Gang Logan
<x xml:space="preserve">Abstract</x> A nanocup structure that mimics the Lycurgus cup effect enables nanoplasmonic spectroscopy to be used for colorimetric sensing, requiring only the naked eye or ordinary visible color photography. Enhanced optical transmission from the subwavelength cup structures couples with the localized surface plasmon from metal nanoparticles on the side walls of the cup, creating extraordinary sensitivity and visible color changes. Utility of the sensor for chemical imaging, biomolecular imaging, and integration to portable microfluidics devices for lab‐on chip‐applications is demonstrated by Liu and co‐workers on page 68. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>